2016
DOI: 10.1007/7651_2016_346
|View full text |Cite
|
Sign up to set email alerts
|

Agent-Based Modeling of Cancer Stem Cell Driven Solid Tumor Growth

Abstract: Computational modeling of tumor growth has become an invaluable tool to simulate complex cell-cell interactions and emerging population-level dynamics. Agent-based models are commonly used to describe the behavior and interaction of individual cells in different environments. Behavioral rules can be informed and calibrated by in vitro assays, and emerging population-level dynamics may be validated with both in vitro and in vivo experiments. Here, we describe the design and implementation of a lattice-based age… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Some of the model parameters had been estimated in previous studies. Specifically, this applies to the maximum proliferation capacity of nonstem cells (tumor cells and immune cells alike), which we set to 10 analogous to (14). Also, it was previously shown that the maximum number of kills a lymphocyte can deliver can be validly estimated as five (23).…”
Section: Estimation Of Key Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the model parameters had been estimated in previous studies. Specifically, this applies to the maximum proliferation capacity of nonstem cells (tumor cells and immune cells alike), which we set to 10 analogous to (14). Also, it was previously shown that the maximum number of kills a lymphocyte can deliver can be validly estimated as five (23).…”
Section: Estimation Of Key Parametersmentioning
confidence: 99%
“…Although these models simplify many aspects of reality, they have been shown to be extremely useful in a wide number of circumstances (10)(11)(12). In cancer research, these models are emerging as valuable tools to study emergent behavior in complex ecosystems (13), especially in stem-cell models of tumor growth (14,15) and are used to study the mutational landscape of solid tumors (16,17). Furthermore, they are increasingly used to optimize therapies, for example radiation therapy of solid tumors (18).…”
Section: Introductionmentioning
confidence: 99%
“…This need is actual both in vascular field as several times demonstrated by different group of investigators [911], but also more in general in the world of computational models developed to replicate pathophysiological phenomena [12]. …”
Section: Introductionmentioning
confidence: 99%
“…So-called in silico trials aimed to predict patient-specific responses to various dose schedules or treatment combinations are becoming an invaluable tool to optimize patient care [11][12][13] . Agent-based tumour growth models are commonly used to describe the behaviour and interaction of individual cells in different environments 14,15 . Among continuous models, the use of ordinary differential equations (ODE) is an useful tool to simulate the evolution of total tumour cell number over time, though it lacks of spatial considerations 16 .…”
Section: Introductionmentioning
confidence: 99%